Muon tomography for railway tunnel imaging - L. F. Thompson; J. P. Stowell; S. J. Fargher; C. A. Steer; K. L. Loughney; E. M. O'Sullivan; J. G. Gluyas; S. W. Blaney; R. J. Pidcock (Physical Review Research, 2020)
Cosmic ray muon radiography utilizes highly penetrating cosmic ray muons to image the density profile of an object of interest. Here we report on a trial to use a portable field-deployable cosmic ray muon tracking system in order to image the whole overburden of a UK railway tunnel with short-duration scans (c. 30 min). An unknown overburden void was identified and, after trial, confirmed by railway authorities. These experiments demonstrate the identification of hidden construction shafts with high levels of statistical significance as density anomalies within the data.